Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Bagi Pelaku UMKM Wilayah Binjai & Langkat Sebagai Upaya Peningkatan Legalitas Usaha - Lina Arliana Nur Kadim; Husnul Khair; Kristina Annatasia; Indah Ambarita; Magdalena Simanjuntak; Melda Pita Uli Sitompul; Ratih Puspadini; Ameliana Sihotang; Zira Fatmahira; Suci Ramadani; Suria Alamsyah Putra (Yayasan Cita Cendikiawan Al Kharizmi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in strengthening the national economy, particularly in job creation and local economic resilience. However, many MSME actors still face administrative constraints, especially in obtaining a Business Identification Number (NIB), which is a mandatory legal requirement for formal business operations through the Online Single Submission (OSS) system. Limited digital literacy and lack of understanding regarding licensing procedures often become the main obstacles. This community service activity aims to provide assistance and guidance to MSME actors in the process of registering and obtaining their Business Identification Number (NIB) through the OSS system. The implementation method consisted of socialization sessions, technical training, direct mentoring, and evaluation. Participants were guided step-by-step in preparing required documents, creating OSS accounts, and completing the NIB registration process. The activity also involved active participation from students as facilitators under academic supervision. The results showed an increase in participants’ understanding of business legality and successful issuance of NIB for assisted MSMEs. Participants demonstrated improved confidence in operating legally and accessing broader business opportunities. The implementation of this mentoring program contributes to strengthening MSME legal compliance, improving digital administrative capabilities, and supporting government programs in accelerating formalization of small businesses. Keywords: UMKM, NIB, OSS, Business Legality